Chemical Synthesis and Structural and Magnetic Properties of Fine Grain Cobalt Substituted Lithium-Nickel-Zinc Nanostructured Ferrites - Pathan, A.T.; Bhandaree, M.R.; Chougule, B.K.; Shaikh, A.M. (Asian Journal of Chemistry, 2012)
A series of cobalt substituted Li-Ni-Zn ferrites with the general formula Li0.5Ni0.25-x/2 Cox/2 Zn0.5 Fe2O4 (where x = 0, 0.1, 0.2, 0.3, 0.4 and 0.5) were prepared by the novel self-propagating auto combustion method. The samples were sintered at 600 ºC before studying their structural and magnetic properties. Phase identification confirmed by XRD showed the formation of cubic spinel structure without any impurities. The average particle size calculated by Scherrer’s formula and lies between 17-24 nm confirms the nano crystalline nature of the samples. The lattice parameter increases with increase of cobalt content. The dependence of porosity with cobalt content was also studied. The SEM micrographs reveal fine-grained ferrites with little agglomeration. The tetrahedral and octahedral ion complexes/vibrations were studied by FTIR. The semiconducting behaviour of ferrite was confirmed by DC resistivity measurements. The resistivity is found to decrease with increase in temperature. The saturation magnetization (Ms), coercive field (Hc) and remanance ratio (Mr/Ms) were measured by using high field hysteresis loop tracer and their variation with composition has been studied. The saturation magnetization decreases with decreasing particle size. The decrease in magnetization results from non-magnetic layer, existing at the surface of the ferrite particles. As the particles size becomes smaller, a super paramagnetic behaviour appears.